UPAYA GURU MENGATASI KEJENUHAN BELAJAR SEJARAH KEBUDAYAAN ISLAM PADA SISWA DI MADRASAH IBTIDAIYAH NEGERI 22 HULU SUNGAI TENGAH - Hatmiah Hatmiah (CV. ADIBA AISHA AMIRA, 2023)
The teacher’s efforts to overcome the saturation of studying Islamic Cultural History in students are needed so that the learning process can be carried out well and students can learn with enthusiasm and fun. Based on this statement, the focus of this study is the teacher’s efforts to address the saturation of learning Islamic cultural history at Madrasah Ibtidaiyah Negeri 22 Hulu Sungai Tengah and its supporting and inhibiting factors. The purpose of this study was to find out the teacher’s efforts in addressing the saturation of learning the history of Islamic culture at Madrasah Ibtidaiyah Negeri 22 Hulu Sungai Tengah as well as the supporting and inhibiting factors. The type of research used is field research and uses a qualitative descriptive approach. The data source for this research was one of the Islamic Cultural History subject teachers, 6 students, school principals, administrative staff, and data relating to the issues discussed. Data collection techniques are carried out by means of observation, interviews, and documentation. The data processing uses data reduction, data display, and data verification. Then analyzed using descriptive qualitative method. The results showed that the teacher’s efforts to overcome the saturation of learning the history of Islamic culture to students at Madrasah Ibtidaiyah Negeri 22 Hulu Sungai Tengah were quite good by packaging learning with rewards and then also providing stimulus in the form of questions that provoke students and giving appreciation to active students. The factors that support and hinder it are: 1) The teaching experience of Islamic Cultural History teachers is long enough so that when teaching is experienced enough and it is easier to convey learning material. 2) Facilities and infrastructure at Madrasah Ibtidaiyah Negeri 22 Hulu Sungai Tengah are sufficient for the teaching and learning process. 3) School Environment The situation and conditions at the Madrasah Ibtidaiyah Negeri 22 Hulu Sungai Tengah are not supportive because it is located close to residential areas so of course it can become an obstacle to the learning process.